1970
DOI: 10.1029/ja075i022p04299
|View full text |Cite
|
Sign up to set email alerts
|

Ogo 4 spectrometer measurements of the tropical ultraviolet airglow

Abstract: The Ogo 4 ultraviolet spectrometer measured the ultraviolet nightglow at tropical latitudes. The spectrum consists of the 1304‐ and 1356‐A lines of atomic oxygen. The Lyman‐Birge‐Hopfield bands of molecular nitrogen and the ultraviolet lines of atomic nitrogen do not appear. The tropical ultraviolet airglow occurs in two bands north and south of the geomagnetic equator under satellite observation conditions that are best correlated with a local time of 2100 to 2130. When the intensity of this airglow is maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The OI 135.6 nm emission from the low latitude ionosphere was first observed by the OGO-4 satellite, and it was observed that the low-latitude ionosphere had two emission peaks located 10°-20°from the geomagnetic equator corresponding to peaks of the plasma density of the equatorial anomaly (EA) or a.k.a. Appleton anomaly (Hicks and Chubb 1970;Barth and Schaffner 1970). Huba et al (2002) reported that the O + density deduced from the OI 135.6 nm limb scan data agrees well with the SAMI2 ionosphere model.…”
Section: Nighttime Ionospheresupporting
confidence: 68%
“…The OI 135.6 nm emission from the low latitude ionosphere was first observed by the OGO-4 satellite, and it was observed that the low-latitude ionosphere had two emission peaks located 10°-20°from the geomagnetic equator corresponding to peaks of the plasma density of the equatorial anomaly (EA) or a.k.a. Appleton anomaly (Hicks and Chubb 1970;Barth and Schaffner 1970). Huba et al (2002) reported that the O + density deduced from the OI 135.6 nm limb scan data agrees well with the SAMI2 ionosphere model.…”
Section: Nighttime Ionospheresupporting
confidence: 68%
“…Since the theoretical calculations can hardly account for such high intensities, we will examine whether a correction should be applied to the preflight calibration. The basis of the discussion is to compare intensities of the 1304-• emissions or other features observed by this instrument with the results of other measurements made under similar conditions, as was suggested initially by Barth and Schaffner [1970].…”
Section: Absolute Emission Rates Of the 1304-• Equatorial Airglowmentioning
confidence: 99%
“…In recent years, the nature of the intertropical arcs has also been studied in the ultraviolet region (Hicks and Chubb, 1970;Barth and Schaffner, 1970), particularly the OI lines at 1304 and 1356A, and this has added a new dimension to the study of the equatorial airglow. A number of suggestions have been made for the possible origin of the ultraviolet airglow in the equatorial region, ranging from the chemical processes involving radiative recombination to the direct excitation of atomic oxygen by the precipitating energetic particles (Hanson, 1969;Hicks and Chubb, 1970;Barth and Schaffner, 1970;Knudsen, 1970;Olson, Peterson and Mosley, 1971;Zipf and Stone, 1971).…”
Section: Introductionmentioning
confidence: 99%